More than meets the eye: Nocardia farcinica, Candida dubliniensis and Aspergillus spp. co-infection in a patient with multiple myeloma treated with multiple treatment regimens - Lotte Vrijders; Erwin Ho; Danielle Van der Beek; Inge Vrelust; Heleen Nailis (BMC Infectious Diseases)
Abstract Background Invasive infections by Nocardia farcinica, Aspergillus species (spp.) and Candida dubliniensis are rare infectious complications in patients diagnosed with multiple myeloma. Case presentation. In this case report, we describe a patient who received three lines of therapy, with proteasome inhibitors, corticosteroids, cyclophosphamide and lenalidomide, and who was concurrently infected with these three opportunistic pathogens. A blood stream infection with C. dubliniensis was treated with 4 weeks of anidulafungin. Aspergillus spp. was treated for 12 weeks with voriconazole. N. farcinica treatment was continued indefinitely with co-trimoxazole and moxifloxacin after regression at discharge of brain abscesses and the pulmonary aspergilloma. Conclusion The diagnostic challenges and management in this particularly vulnerable patient are highlighted.